Macroalgae composition of the “Bostrychietum” from two different mangrove areas of the State of Pernambuco, Brasil. - Fontes, Khey Albert de Azevedo (2007)
Aiming at analyzing the structure and distribution of macroalgal communities inside “Bostrychietum” from two different areas, one preserved and another moderately impacted, from the Pernambuco coast, Brazil, to aim for observing efficient parameters for environmental monitoring processes of mangrove areas, five line transects (mangrove fringes long) were performed in each of the study sites during the low tide in March/2004 (03/22 in Vila Velha and 03/24 in Suape. A total of 15 species were identified from the two areas (six clorophytes and nine rodophytes). Macroalgae composition from “Bostrychietum” from the two study sites were similar to other “Bostrychietum” areas studied in Brazil and around the world. Vila Velha has been registered having the largest number of species as well as highest total biomass values. A significant biomass trend of biomass increasing from seaward to landward was observed. Red algae were most frequent at the high region of the pneumatophores while green algae were most frequent at the low ones. The results suggest that “Bostrychietum” can be applied to environmental monitoring processes inside impacted mangrove areas.